Anthocyanin Activity of Red Dragon Fruit (Hylocereus polyrhizus) Peel as Immunostimulan in the Covid-19 Pandemic Era - Fitriyani Fitriyani; Lisa Aulia Zahra; Istifadah Istifadah (Jurnal Kesehatan Metro Sai Wawai, 2022)
Background: Coronavirus disease (Covid-19) are generally self-limiting diseases that rely on immune power. Certain food nutrients can be essential in maintaining health and boosting the immune system. One of the nutrients that can maintain and boost the immune system is a flavonoid, which is found in the peel of the red dragon fruit (Hylocereus polyrhizus). The red dragon fruit peel is rich in polyphenols and anthocyanins-flavonoid, which are sources of antioxidants. Dragon fruit peel waste is developed and processed into innovative food in the form of “bakpao” as a source of nutrition and adds to the public's attractiveness, which is then labelled the product "Dragon Pao". Purpose: To help people choose food innovations that can help them increase their immunity in the Covid-19 pandemic era. Methods: This study uses a laboratory study with a qualitative approach followed by several tests of substances in the bakpao product from red dragon fruit peel. The intended tests are organoleptic, hedonic, and anthocyanin tests. The total number of panellists used for the hedonic test  was 20 people in the Malang area. Panellists were randomly selected and came from various age groups. The hedonic test was carried out using a google form through a questionnaire. Result: The results of the organoleptic test obtained a soft texture, a distinctive smell of meatballs, a pink colour, and a sweet taste. Hedonic test results obtained 80-90% of respondents' answers are in the options like and really like. Then in the anthocyanin test, the dragon fruit peel was positive for anthocyanin. Conclusion: Dragon Pao” have the potential to be a nutraceutical product as an immunostimulant in the Covid-19 pandemic era that all people like. Consumption of "Dragon Pao" is an option to increase the body's immunity as an effort to prevent exposure to Covid-19.Latar Belakang: Penyakit Coronavirus (Covid-19) umumnya merupakan penyakit self-limiting yang bergantung pada daya tahan tubuh. Nutrisi dalam makanan memiliki peran penting dalam menjaga kesehatan dan meningkatkan sistem kekebalan tubuh. Salah satu nutrisi yang mampu menjaga dan meningkatkan daya tahan tubuh, yaitu flavonoid yang terdapat pada kulit buah naga merah (Hylocereus polyrhizus). Kulit buah naga merah kaya akan polifenol dan antosianin-flavonoid yang merupakan sumber antioksidan. Limbah kulit buah naga dikembangkan dan diolah menjadi makanan inovatif berupa bakpao sebagai sumber gizi dan menambah daya tarik masyarakat, yang kemudian diberi label produk “Dragon Pao”. Tujuan: Membantu masyarakat memilih inovasi pangan yang dapat membantu meningkatkan imunitas di era pandemi Covid-19. Metode: Penelitian ini menggunakan studi laboratorium dengan pendekatan kualitatif yang dilanjutkan dengan beberapa pengujian zat dalam produk bakpao dari kulit buah naga merah. Uji yang dimaksud adalah uji organoleptik, hedonik, dan antosianin. Jumlah panelis yang digunakan untuk uji hedonik adalah 20 orang di wilayah Malang. Panelis dipilih secara acak dan berasal dari berbagai kelompok umur. Uji hedonik dilakukan dengan menggunakan google form melalui kuesioner. Hasil: Hasil uji organoleptik diperoleh tekstur lembut, bau khas bakpao, warna merah muda, dan rasa manis. Hasil uji hedonik diperoleh 80-90% jawaban responden berada pada pilihan suka dan sangat suka. Kemudian pada uji antosianin, kulit buah naga positif mengandung antosianin. Simpulan: “Dragon Pao” berpotensi menjadi produk nutrasetikal sebagai imunostimulan di era pandemi Covid-19 yang disukai oleh semua kalangan. Konsumsi “Dragon Pao” menjadi salah satu pilihan untuk meningkatkan imunitas tubuh sebagai upaya mencegah terpapar Covid-19.